Comparative Analysis of the Use of Pattern Drafting and Free Hand Cutting Methods among Tailors and Apprentices in Kenya and Ghana - Bakker-Edoh , Dymphna; Kassah , Johnson; Kereth, Gudila; Oigo , Elizabeth; Mburugu , Keren (Journal of Marketing Studies, 2022)
Purpose: The study aimed at evaluating comparative analysis of the use of pattern drafting and free hand cutting methods among tailors and apprentices in Kenya and Ghana. Methodology: For this research, the study used a cross-sectional descriptive design. The target population was tailors in Githurai, Kenya and Dwa Kitiwam, Koforidua, Ghana. A sample was drawn randomly from this sampling frame which comprised of 30 tailors, with 15 being from Githurai, Kenya and 15 from Dwa Kitiwam, Koforidua, Ghana. This study further used questionnaires to collect primary data. Data obtained from the field was coded and filtered and systematically sorted according to the questionnaire objects using frequency distributions and proportions. With the aid of the Social Science Statistical Package (SPSS) version 26, the researchers used both descriptive and inferential statistics to analyze the results. Results: Ghana is more inclined to pattern drafting than free hand cutting compared to Kenyan tailors who are inclined to free hand cutting as much as pattern drafting. Proving that the individuals vary in their views on free-hand cutting and pattern drafting revealed that the tendency of dressmakers and tailors for free-hand cutting was affected by the technique with which they were educated and the simplicity associated with free-hand cutting processes. Unique Contribution to Theory, Practice and Policy: Instructors should cultivate the utilization of pattern drawing to acquire a deeper understanding of the skills of pattern drafting